Long-term structural retinal changes in patients with optic neuritis related to multiple sclerosis - Andersen MR (Dove Medical Press, 2017)
Maria Rene Andersen,1 Malte Roar,2,3 Tobias Sejbaek,2,3 Zsolt Illes,2,3 Jakob Grauslund1,3 1Department of Ophthalmology, Odense University Hospital, Odense, Denmark; 2Department of Neurology, Odense University Hospital, Odense, Denmark; 3Department of Clinical Research, University of Southern Denmark, Odense, Denmark Purpose: To evaluate the long-term structural and functional outcome in patients with multiple sclerosis (MS) with and without a history of optic neuritis (ON).Methods: This was a cross-sectional study of 82 patients diagnosed with MS between 2000 and 2006 from a tertiary hospital center in Denmark. Patients gave a self-reported history of ON, and functional (visual acuity and color vision) and structural (spectra domain optical coherence tomography) markers of vision were tested.Results: Median age and MS duration at the time of the clinical examination were 49.9 years (range 30.7–72.6 years) and 13 years (range 9–15 years), respectively. ON was not associated with impairment of visual acuity or color vision. Twenty-three patients had a history of ON in at least one eye. Compared to non-affected patients, these had a lower inferior (109 vs 113 µm, P=0.04) and temporal retinal nerve fiber layer (RNFL) thickness (56 vs 67 µm, P=0.01). In an age- and sex-adjusted logistic regression model, lower inferior and temporal RNFL were associated with a higher risk of ON (odds ratio [OR] 1.56 [95% confidence interval CI 1.01–2.41] and OR 1.74 [95% CI 1.10–2.77] per 10 µm decrement in RNFL thickness, respectively). Twenty patients had a history of ON in one eye. Compared to the non-affected eye, this eye had a lower RNFL (109 vs 115 µm, P=0.04) and a higher central retinal thickness/mean RNFL ratio (2.7 vs 2.4, P=0.04).Conclusion: Although patients with long-term MS and a previous history of ON did not have any functional loss of vision, structural neurodegeneration could be demonstrated in the affected eye. Keywords: optic neuritis, multiple sclerosis, optical coherence tomography, retinal nerve fiber layer, central retinal thickness